Motor Unit Activity during Fatiguing Isometric Muscle Contraction in Hemispheric Stroke Survivors - McManus, Lara; Hu, Xiaogang; Rymer, William Z.; Suresh, Nina L.; Lowery, Madeleine M. (Frontiers in Human Neuroscience, 2017)
Enhanced muscle weakness is commonly experienced following stroke and may be accompanied by increased susceptibility to fatigue. To examine the contributions of central and peripheral factors to isometric muscle fatigue in stroke survivors, this study investigates changes in motor unit (MU) mean firing rate and action potential duration during, and directly following, a sustained submaximal fatiguing contraction at 30% maximum voluntary contraction (MVC). A series of short contractions of the first dorsal interosseous muscle were performed pre- and postfatigue at 20% MVC, and again following a 10-minute recovery period, by twelve chronic stroke survivors. Individual MU firing times were extracted using surface EMG decomposition and used to obtain the spike-triggered average MU action potential waveforms. During the sustained fatiguing contraction, the mean rate of change of the firing rate across all detected motor units was greater on the affected side (-0.02 ± 0.03 Hz/s) than on the less-affected side (-0.004 ± 0.003 Hz/s, p = .045). The change in firing rate immediately postfatigue was also greater on the affected side than less-affected side (-13.5 ± 20 % and 0.1 ± 19 %, p = .04). Mean MU firing rates increased following the recovery period on the less-affected side (19.3 ± 17 %), but not on the affected side (0.5 ± 20 %, p = .03). MU action potential duration increased postfatigue on both sides (10.3 ± 1.2 ms to 11.2 ± 1.3 ms on the affected side and 9.9 ± 1.7 ms to 11.2 ± 1.9 ms on the less-affected side, p = .001 and p = .02, respectively), and changes in MU action potential duration tended to be smaller in subjects with greater impairment (p = .04). This study presents evidence of both central and peripheral fatigue at the motor unit level during isometric fatiguing contraction for the first time in stroke survivors. Together, these preliminary observations indicate that the response to an isometric fatiguing contraction differs between the affected and less-affected side post-stroke, and may suggest that central mechanisms observed here as changes in firing rate are the dominant processes leading to task failure on the affected side.